2016
DOI: 10.12659/msm.896736
|View full text |Cite
|
Sign up to set email alerts
|

Heliox-Driven Nebulization Has a Positive Effect on the Lung Function in Lipopolysaccharide-Induced Chronic Obstructive Pulmonary Disease Rat Model

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a serious lung disease that severely threatens people’s health. This study aimed to investigate the effects of heliox-driven nebulization (HDN) on lung function and arterial blood gases in a COPD rat model.Material/MethodsTwelve healthy male Wistar rats were selected as controls and 34 rats were used to establish a COPD model induced by lipopolysaccharide. Then 6 rats each from the control and model groups were selected for their symptoms to be observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In this study, we found that long-term exposure of PM2.5 resulted in a significant decrease in pulmonary compliance and forced pulmonary ventilation in mice. This result is consistent with previous studies reporting that the dynamic lung compliance is decreased in COPD [ 34 , 35 ]. In accordance with these observations, we found that PM2.5 exposure induced mouse pulmonary emphysema and reduced the mean number of alveoli in the mouse lung.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that long-term exposure of PM2.5 resulted in a significant decrease in pulmonary compliance and forced pulmonary ventilation in mice. This result is consistent with previous studies reporting that the dynamic lung compliance is decreased in COPD [ 34 , 35 ]. In accordance with these observations, we found that PM2.5 exposure induced mouse pulmonary emphysema and reduced the mean number of alveoli in the mouse lung.…”
Section: Discussionsupporting
confidence: 94%
“…Research shows that helium can reduce the inflammatory reaction in lung damage and has anti‐inflammatory effects. Animal experiments have shown that helium can decrease alveolar hemorrhage in mice, neutrophil invasion in lung tissue, edema, and pulmonary hyaline membrane occurrence 38,39 . Many studies suggest that meconium is a potent activator of inflammatory mediators, including cytokines, complement, prostaglandins and reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…With low density and high diffusion, heliox can reduce the occurrence of turbulence in the airway and effectively reduce the airway resistance, subsequently reducing endogenous PEEP and lung volume. In this way, venous return and pulmonary circulation resistance can be relatively stable, and hemodynamic status can be improved to a certain extent [24][25][26]. Therefore in this study, compared with nitrogen-oxygen ventilation at a relatively high PEEP level, heliox ventilation reduced airway pressure and CVP and increased ScvO 2 in older hypertensive patients, without affecting heart rate or causing signi cant uctuations in blood pressure.…”
Section: Discussionmentioning
confidence: 92%
“…Heliox is di cult to prepare, expensive, and easy to escape from tightly sealed containers due to its high diffusion, resulting in high therapeutic cost and limited clinical application [25]. In this study, the hermetic breathing circuit was innovatively applied for heliox ventilation to recycle helium gas.…”
Section: Discussionmentioning
confidence: 99%